1996
DOI: 10.1002/(sici)1096-8628(19960906)64:4<546::aid-ajmg4>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile rheumatoid arthritis in velo-cardio-facial syndrome: Coincidence or unusual complication?

Abstract: We report on two patients with velo‐cardiofacial syndrome (VCFS) and juvenile rheumatoid arthritis (JRA). The first, a 9‐year‐old girl, presented with microcephaly, characteristic face, congenital heart disease, and velopharyngeal insufficiency. Fluorescence in situ hybridization (FISH) study showed deletion of D22S75 (N25), confirming the diagnosis of VCFS. At age 7, she developed joint pain, and polyarticular JRA was diagnosed. Awareness of this case led to the subsequent diagnosis of VCFS (also confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 24 publications
(9 reference statements)
0
10
0
1
Order By: Relevance
“…It appears reasonable that patients with del22q11.2 are predisposed to auto-immune disease as a result of thymic dysfunction. In the literature, two girls have been reported with the association of VCFS and juvenile rheumatoid arthritis [15]. Recently, ITP in two females with del22q11.2 has been described, one of whom has chronic but mild thrombocytopenia like our case 8 [9].…”
Section: Discussionmentioning
confidence: 83%
“…It appears reasonable that patients with del22q11.2 are predisposed to auto-immune disease as a result of thymic dysfunction. In the literature, two girls have been reported with the association of VCFS and juvenile rheumatoid arthritis [15]. Recently, ITP in two females with del22q11.2 has been described, one of whom has chronic but mild thrombocytopenia like our case 8 [9].…”
Section: Discussionmentioning
confidence: 83%
“…Currently, there are no biomarkers to identify or predict which patients will develop autoimmune features [71]. A range of autoimmune features have been described including cytopenias, systemic autoimmunity, particularly rheumatoid arthritis, and organspecific autoimmunity, most notably autoimmune thyroid disease [71,83,84,86,[94][95][96][97]. Other immunological abnormalities, including IgA deficiency may be associated [85].…”
Section: Presenting and Immunological Featuresmentioning
confidence: 99%
“…Pinchas et al [17] observed in a 5-year-old girl with DGS, a liver disease with epitheliod granulomata, smooth muscle Study showed decreased lifespan and splenic sequestration antibodies and mononuclear cell infiltrate supporting the diagnosis of granulomatous hepatitis, of probable auto-immune origin. Rasmussen et al [18] described the occurrence of juvenile rheumatoid arthritis in two children with VCFS.…”
Section: Discussionmentioning
confidence: 99%
“…Now, this concept is not sufficient to embrace all the phenotypic forms of the 22q11 microdeletion -the term ''22q11.2 deletion syndrome'' is now widely used [2,15,19]. A few observations of auto-immune disorders have been reported in patients with the 22q11 deletion [1,3,8,11,13,17,18]. To the best of our knowledge, six observations of auto-immune cytopenia have been reported in the literature [1,3,13,17].…”
Section: Introductionmentioning
confidence: 99%